Antecedents of loyalty intentions among young adult tourists: A survey - Elżbieta Wąsowicz-Zaborek (International Journal of Management and Economics, 2019)
The purpose of this paper was to examine the antecedents of young adult tourists' loyalty intentions. The study is concerned with the overall loyalty tendencies of individuals, comprising the two dimensions of revisit intentions (RVIs) and recommendation intentions (RIs), and thus does not explore their loyalty to a specific destination (as in most previous studies). The research uses an Internet questionnaire with a total sample of 305 university students recruited from two Polish universities. Statistical analysis with the partial least squares structural equation modeling method indicates that destination RI is mainly driven by social bonding, while RVI is influenced positively by risk and uncertainty avoidance and negatively by novelty and variety seeking. In addition, income is found to be a significant moderator in the relationship between risk and uncertainty perception and RIs, such that a transition from very low to very high incomes tends to reverse the focal relationship from positive to negative. In addition, the research demonstrates that there is no significant difference between male and female young tourist's loyalty intention. Implications for tourism entrepreneurs and destinations are suggested in the concluding section of the article.
Keywords: Z32; Z33; M31; 650; loyalty in tourism; destination loyalty; recommendation intention; revisit intention; PLS-SEM